2017
DOI: 10.1007/s00216-017-0772-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent mass spectrometry-based techniques and considerations for disulfide bond characterization in proteins

Abstract: Disulfide bonds are important structural moieties of proteins: they ensure proper folding, provide stability, and ensure proper function. With the increasing use of proteins for biotherapeutics, particularly monoclonal antibodies, which are highly disulfide bonded, it is now important to confirm the correct disulfide bond connectivity and to verify the presence, or absence, of disulfide bond variants in the protein therapeutics. These studies help to ensure safety and efficacy. Hence, disulfide bonds are among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 117 publications
(192 reference statements)
2
87
1
2
Order By: Relevance
“…Additional reports further support the conclusion that these breakages, along with any sequential bond formation, can affect the stability of mAbs. [65][66][67] However, given the absence of any disulfide mapping approach in our study, such as those previously reported in the literature, 68 we cannot conclusively support our hypothesis using CIU-IM-MS data alone.…”
Section: Discussioncontrasting
confidence: 58%
“…Additional reports further support the conclusion that these breakages, along with any sequential bond formation, can affect the stability of mAbs. [65][66][67] However, given the absence of any disulfide mapping approach in our study, such as those previously reported in the literature, 68 we cannot conclusively support our hypothesis using CIU-IM-MS data alone.…”
Section: Discussioncontrasting
confidence: 58%
“…Du et al stated that during the manufacturing process, extensive reduction of antibodies has been observed after harvest operation or Protein A affinity chromatography and multiple process parameters correlate to the extent of the reduction [34]. The topic "disulfide bonds of therapeutic proteins" is in depth discussed by Lakbub et al [35].…”
Section: Analysis Of Proteoforms Of Recombinant Therapeutic Proteinsmentioning
confidence: 99%
“…Therefore, it is useful and necessary (in cases where the MS/MS assignments are ambiguous) to confirm the disulfide bond assignments using the protocol described here. A recent comprehensive review of MS‐based techniques summarizes and compares most bottom‐up techniques and associated software for disulfide bond assignment (Lakbub, Shipman, & Desaire, ).…”
Section: Strategic Planningmentioning
confidence: 99%